Choriocarcinoma in Women: Analysis of a Case Series With Genotyping. (December 2017) - Savage, Johanna; Adams, Emily; Veras, Emanuela; Murphy, Kathleen M.; Ronnett, Brigitte M.
Abstract : Choriocarcinoma is an uncommon malignant neoplasm, which can be either gestational or nongestational in origin. Distinction of these subtypes has prognostic and therapeutic implications. Twenty-two tumors were genotyped using polymerase chain reaction amplification of 15 short tandem repeat loci and the amelogenin locus (XY determination). DNA patterns from tumor and maternal tissue, as well as villous tissue from any available prior or concurrent gestation, were compared, to determine gestational versus nongestational nature (containing vs. lacking a paternal chromosome complement, respectively) and the relationship between the tumor and any prior or concurrent gestation. Nineteen tumors were gestational. Of these, 14 were purely androgenetic/homozygous XX: 6 uterine tumors with a concurrent or prior genetically related complete hydatidiform mole (CHM), 4 uterine tumors without an accompanying villous component, 1 uterine cornual tumor separate from a genetically distinct second trimester intrauterine placenta, 1 ectopic ovarian tumor separate from a genetically distinct third trimester intrauterine placenta, and 2 ectopic fallopian tube tumors. Five gestational tumors were biparental: 3 (2 XX, 1 XY) intraplacental choriocarcinomas genetically related to the placenta and 2 uterine tumors without accompanying placental tissue after term deliveries (1 XX 4 weeks postpartum and 1 XYY with allelic imbalances 1 year postpartum; prior placentas not available for analysis). Three tumors were nongestational: all XX with allelic imbalances; 2 ovarian, 1 pelvic. Gestational choriocarcinoma can be androgenetic or biparental. Most are androgenetic/homozygous XX, often associated with a genetically related concurrent or prior CHM, and thus of molar-associated type. These findings support that homozygous XX CHMs are associated with some risk of significant gestational trophoblastic disease. Intraplacental choriocarcinomas are biparental and genetically related to the placenta. Biparental choriocarcinoma detected in a postpartum uterine sample is consistent with undetected intraplacental choriocarcinoma. Eutopic or ectopic androgenetic choriocarcinoma separate from a concurrent intrauterine placenta is not derived from intraplacental tumor and is consistent with either a form of dispermic twin gestation (molar-type choriocarcinoma and coexistent nonmolar fetus) or origin from an antecedent molar pregnancy. While fallopian tube tumors are usually gestational, tumors in other sites (ovary, pelvis) can be nongestational and should not be assumed to be metastatic from a regressed or occult intrauterine or intraplacental gestational tumor.